Quercetin-3-O-glucuronide in the Ethanol Extract of Lotus Leaf (Nelumbo nucifera) Enhances Sleep Quantity and Quality in a Rodent Model via a GABAergic Mechanism - Singeun Kim; Ki-Bae Hong; Kyungae Jo; Hyung Joo Suh (Molecules, 2021)
Current pharmacological treatments for insomnia carry several and long-term side effects. Therefore, natural products without side effects are warranted. In this study, the sleep-promoting activity of the lotus leaf (Nelumbo nucifera) extract was assessed using ICR mice and Sprague Dawley rats. A pentobarbital-induced sleep test and electroencephalogram analysis were conducted to measure sleep latency time, duration, and sleep architecture. The action mechanism of the extract was evaluated through ligand binding experiments. A high dose (300 mg/kg) of the ethanolic lotus leaf extract significantly increased sleep duration compared to the normal group (p < 0.01). Administration of low (150 mg/kg) and high doses (300 mg/kg) of the extract significantly increased sleep quality, especially the relative power of theta waves (p < 0.05), compared to the normal group. Furthermore, caffeine and lotus leaf extract administration significantly recovered caffeine-induced sleep disruption (p < 0.001), and the sleep quality was similar to that of the normal group. Additionally, ligand binding assay using [3H]-flumazenil revealed that quercetin-3-O-glucuronide contained in the lotus leaf extract (77.27 μg/mg of extract) enhanced sleep by binding to GABAA receptors. Collectively, these results indicated that the lotus leaf extract, particularly quercetin-3-O-glucuronide, exhibits sleep quantity- and quality-enhancing activity via the GABAergic pathway.